Pelaksanan Peran Badan Permusyawaratan Desa (BPD)Dalam Pengawasan Kinerja Pemerintah Desa Di Desa Silimabanua Kecamatan Tuhemberua Kabupaten Nias Utara: Abstract,Abstrak,1.LATAR BELAKANG,2. KAJIAN TEORITIS,3. METODE PENELITIAN,4. HASIL DAN PEMBAHASAN, 5. KESIMPULAN DAN SARAN,DAFTAR REFERENSI - Gea, Atia; Westika Putri, Sinta (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to describe the implementation of the role of the Village Consultative Body (BPD) in supervising village government performance and to identify the supporting and inhibiting factors affecting the implementation of such supervision. This research employed a qualitative approach with a descriptive method. Research informants were selected using purposive sampling techniques involving village government officials, BPD members, and community leaders. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing using source and technique triangulation. The results indicate that BPD has carried out its supervisory role through monitoring activities, evaluation, discussion of village government administration reports, and the channeling of community aspirations. However, the implementation of this role has not been fully comprehensive due to limited BPD involvement in several stages, inconsistent coordination between BPD and the village government, the absence of a structured mechanism for channeling community aspirations, and challenges related to BPD members' understanding of regulations and village financial management. Supporting factors include a clear legal framework, the commitment of BPD members, and community support. Meanwhile, inhibiting factors include limited human resource capacity, inadequate transparency of village government information, lack of inter-institutional coordination, and low community participation in the supervision process. Keywords: Village Consultative Body; supervision; village government performance; village governance; community participation.